2018
DOI: 10.1038/s41366-018-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ considerable underestimation of sugar and their child’s risk of overweight

Abstract: High sugar intake is associated with an increased risk of overweight. For parents, as their children's nutritional gatekeepers, knowledge about sugar is a prerequisite for regulating sugar consumption. Yet little is known about parental ability to estimate the sugar content of foods and beverages and how this ability is associated with children's body mass index (BMI). In 305 parent-child pairs, we investigated to what extent parents systematically under- or overestimate the sugar content of foods and beverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
0
17
1
1
Order By: Relevance
“…Recent research has shown that the vast majority of parents significantly underestimate the sugar content of common food items in children's diets and the degree of parental underestimation of sugar was associated with risk of overweight and obesity [28]. Notably, of the six foods tested in the study, yogurt was the food the majority of parents (92% of 305) underestimated the most, by "seven sugar cubes" [28]. The authors attribute this to the 'health halo effect', whereby the sugar contents of perceived healthy foods are underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the vast majority of parents significantly underestimate the sugar content of common food items in children's diets and the degree of parental underestimation of sugar was associated with risk of overweight and obesity [28]. Notably, of the six foods tested in the study, yogurt was the food the majority of parents (92% of 305) underestimated the most, by "seven sugar cubes" [28]. The authors attribute this to the 'health halo effect', whereby the sugar contents of perceived healthy foods are underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this relative deviation, underestimation was defined as a relative deviation lower than 0, while overestimation was defined as a relative deviation greater than 0 (c.f. [10]). Estimations were accurate if relative deviation equalled 0.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that many consumers struggle to estimate accurately foods’ nutritional value: A study that specifically investigated estimations of sugar content showed that the majority of participants underestimated the sugar content of four out of six food items, although there was some variation in the under- and overestimation of sugar content between foods [10]. Other studies that investigated estimations of a meal’s energy content showed a general underestimation that increased with meal size [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Parents are their children’s nutritional gatekeepers, their knowledge and choices determine what their children eat (e.g. Dallacker et al 2016 ; 2018 ). Children have little control over purchases and generally eat the food that is available at home (Lopez et al 2012 ; Elfhag et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%